SENTIMENT ANALYSIS ON HALAL INVESTMENT - Sari, Mia (Indonesian Scientific Journal of Islamic Finance, 2024)
As a country with a majority Muslim population, Indonesia should be at the center of sharia economic development in the world. The potential is also quite large, starting from halal certification, concern for Muslim-friendly products, services that make it easier for Muslims to practice their beliefs, and much more. The strategy to achieve Indonesia's vision as the world's leading sharia economic center is to strengthen the halal value chain. This study examines Halal Investment as a component that is fundamental to the development of the halal industry in Indonesia. Based on the available literature, it was found that there is no sentiment research on this topic. The method used is descriptive statistical analysis with meta-analysis and sentiment analysis of secondary data in the form of metadata from 41 Scopus indexed publications published in the last 25 years, starting in 1997 and ending in 2022. The results of the sentiment analysis show that the response to the development of halal investment tended to vary, with positive sentiment at 41.5%, negative sentiment at 17.1%, and neutral sentiment at 39.0%. This study also attempts to identify negative responses to halal investments and offers ideas for future research.